Choctaw prophecy : a legacy of the future - Mould, Tom, 1969- (Contemporary American Indian studies., 2003)
Annotation This intriguing study explores the power and artistry of prophecy among the Mississippi Band of Choctaw Indians, who use predictions about the future to interpret the world around them. This book challenges the common assumption that American Indian prophecy was an anomaly of the 18th and 19th centuries that resulted from tribes across the continent reacting to the European invasion. Tom Mould's study of the contemporary prophetic traditions of the Mississippi Band of Choctaw Indians reveals a much larger system of prophecy that continues today as a vibrant part of the oral tradition. Mould shows that Choctaw prophecy is more than a prediction of the future; it is a way to unite the past, present, and future in a moral dialogue about how one should live. Choctaw prophecy, he argues, is stable and continuous; it is shared in verbal discourse, inviting negotiation on the individual level; and, because it is a tradition of all the people, it manifests itself through myriad visions with many themes. In homes, casinos, restaurants, laundromats, day care centers, and grocery stores, as well as in ceremonial and political situations, people discuss current events and put them into context with traditional stories that govern the culture. In short, recitation is widely used in everyday life as a way to interpret, validate, challenge, and create the world of the Choctaw speaker. Choctaw Prophecystands as a sound model for further study into the prophetic traditions of not only other American Indian tribes but also communities throughout the world. Weaving folklore and oral tradition with ethnography, this book will be useful to academic and public libraries as well as to scholars and students of southern Indians and the modern South.